2007
DOI: 10.1002/adma.200602936
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biohybrid Materials by Electrospinning: Nanofibers of Poly(ethylene oxide) and Living Bacteria

Abstract: Electrospinning is a versatile method for the preparation of continuous fibers with diameters ranging from micrometers down to a few nanometers.[1] Nonwovens of electrospun fibers are obtained from polymer solution or melt when a materials jet moves from an electrode to the corresponding counter electrode under the influence of a strong electrical field (up to several kV cm -1 ) with simultaneous evaporation of solvent or solidification of melt. Although the experimental set-up is simple the process is complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
54
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 11 publications
4
54
0
Order By: Relevance
“…In former studies bioactive ingredients such as proteins and DNA have been embedded successfully in nanofibers mainly for tissue engineering purposes, while living prokaryotic cells were encapsulated by this technique mainly for industrial application in bioreactors utilizing their metabolic activity [20][21][22]. Zussman [23] has recently reviewed the preparation methods of electrospun polymer fibers encapsulating cells and their potential applications.…”
mentioning
confidence: 99%
“…In former studies bioactive ingredients such as proteins and DNA have been embedded successfully in nanofibers mainly for tissue engineering purposes, while living prokaryotic cells were encapsulated by this technique mainly for industrial application in bioreactors utilizing their metabolic activity [20][21][22]. Zussman [23] has recently reviewed the preparation methods of electrospun polymer fibers encapsulating cells and their potential applications.…”
mentioning
confidence: 99%
“…As described earlier, electrospinning is an efficient method for encapsulating bacteria in the polymer fiber. However, in the electrospinning process, the removal of water by rapid evaporation is anticipated to cause drastic changes in the osmotic environment of the organism (23). Furthermore, an electric field, which may be harmful to the bacteria, is generated by applying a high voltage between the metal capillary and the collector.…”
Section: Resultsmentioning
confidence: 99%
“…If these mechanical and biocompatible properties are combined with the high surface-to-volume ratios of fibers, the hydrogel can be used as an efficient support material both for enzymes and for immobilization of microorganisms (20). Lee and Belcher (21), Salalha et al (22), and Gensheimer et al (23) had investigated electrospinning as a possible method of encapsulating both bacteria and bacterial viruses. Although these studies are of great value and showed the promise of this emerging field, the electrospun polyvinyl alcohol, PEO, and polyvinyl pyrrolidone materials were water soluble, and thus their use was significantly limited.…”
mentioning
confidence: 99%
“…As the composites obtained in other ways, these nanocomposites are classified by the nature of interaction between organic and inorganic phases: nanocomposites with interphase covalent bond [92][93][94] and nanocomposites with weak (for example, hydrogen) bonds between the phases [95][96][97]. There are quite many examples in which these types of nanocomposites are described and characterized, we shall confine just to some of them [98][99][100][101][102][103][104][105][106][107][108][109][110]. Class 5 by classification [49] from Table 4.2 belongs to this type of materials They include hard metal oxide polymer and organic polymer capable of binding metal ions, thus forming metal-polymer complex.…”
Section: Formation Of Inorganic Precursor In Presence Of Organic Polymentioning
confidence: 99%